Planejamento, síntese e avaliação farmacológica de novos compostos 1,2,5-oxadiazol-2-n-óxido úteis como preventivos de aterotrombose - Dutra, Luiz Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Cardiovascular diseases such as myocardial infarction and stroke still represents the leading cause of death in Brazil. Atherosclerosis is a silent progressive disease classified as a risk factor for developing cardiovascular diseases. It is characterized by increased levels of plasma cholesterol which are oxidized by free radicals resulting in oxidized low density lipoprotein (oxLDL). The oxLDL phagocytosis by macrophages allows for transformation into foam cells, which are deposited in the intima of vessels. After the disruption of the endothelium occurs the leak plaque’s contents into the circulation driving to thrombus formation. This blocks the blood flow in arteries and vessels, leading to the development of cardiovascular diseases such as myocardial infarction and stroke. The preventive therapy against atherothrombotic events is performed with antiplatelet drugs. Acetylsalicylic acid (ASA) is a drug commonly used to prevent atherothrombosis, but it has limitations such as induction of gastric ulcer and blocking only one route of platelet aggregation. Continuing goals finding new antiplatelet drugs obtained by molecular modification strategy implemented in the Laboratory of Drug Research and Development (Lapdesf - UNESP Araraquara), held the molecular hybridization of subunits present in AAS and furoxans being spaced by subunit N-acylhydrazone. The furoxano is known for its donor properties of nitric oxide (NO) responsible for the antiplatelet effect. The objective of this work is the synthesis of new compounds derived from AAS, most powerful and safe to use as antiplatelet agents. Compounds were synthesized using divergent route for obtaining derivatives furoxans, N-acilhidrazones spacers and the hybrid compounds. All compounds were purified and characterized by analytical methods such as, Infrared Absorption Spectroscopy, Mass Spectrometry and Nuclear Magnetic Resonance. N-acilhidrazones spacers was possible to perform the ...

Doenças cardiovasculares como infarto do miocárdio e acidente vascular encefálico ainda representam a principal causa de morte no Brasil. A aterosclerose é uma doença progressiva e silenciosa classificada como fator de risco para o desenvolvimento de doenças cardiovasculares. É caracterizada pelo aumento dos níveis de colesterol no plasma os quais são oxidados por radicais livres originando a lipoproteína de baixa densidade oxidada (LDLox). A fagocitose de LDLox por macrófagos permite a transformação destes em células espumosas, que são depositadas na camada íntima dos vasos. Após o rompimento do endotélio há o extravasamento do conteúdo da placa aterosclerótica para a circulação levando à formação de trombo. Este interrompe o fluxo sanguíneo em artérias e vasos, levando ao desenvolvimento de doenças cardiovasculares como infarto do miocárdio e acidente vascular encefálico. A terapia preventiva contra eventos aterotrombóticos é realizada com fármacos antiagregantes plaquetários. O ácido acetilsalicílico (AAS) é um dos fármacos mais utilizados na prevenção de aterotrombose, mas apresenta limitações como indução de ulcerações gástricas e bloqueio de somente uma via de agregação plaquetária. Neste sentido, e em continuidade com a linha de pesquisa visando à busca de novos fármacos antiagregantes plaquetários obtidos por estratégia de modificação molecular implantados no Laboratório de Pesquisa e Desenvolvimento de Fármacos (Lapdesf – UNESP Araraquara), realizou-se a hibridação molecular das subunidades presentes no AAS e furoxanos sendo ambas partes espaçadas pela subunidade N-acilhidrazona. O furoxano é conhecido por suas propriedades doadoras de óxido nítrico (NO) responsável pelo efeito antiagregante plaquetário. Assim, o objetivo deste trabalho é a síntese de novos compostos derivados do AAS, mais potentes e seguros para serem usados como antiagregantes plaquetários. Os ...
Keywords: Aterosclerose; Sistema cardiovascular - Doenças; Infarto do miocárdio; Myocardial infarction